Climate change and automation: The emission effects of robot adoption - Ana Lucia Abeliansky; Klaus Prettner; Ernesto Rodríguez-Crespo (University of Economics in Bratislava, Department of Economic Policy, 2024)
What are the environmental impacts of the increasing use of automation technologies? To answer this question, we propose a model of production in the age of automation that incorporates emission externalities. We derive a threshold condition subject to which the use of industrial robots affects emissions. This model leads to three testable predictions, i) the use of industrial robots causes higher emissions on average, ii) with increasing efficiency of industrial robots, the effect becomes weaker and could turn negative, and iii) in countries in which electricity is predominantly produced using (clean) renewable energy, industrial robot use has the potential of decreasing emissions. Empirically, we find support for the theoretical hypotheses implying that the effect of automation on emissions is non-linear or moderated by other variables.
Keywords: O11; O33; O44; Q54; Q55; Q56; 330; Automation; Robots; Emissions; Climate Change